2021
DOI: 10.1177/0748730421999870
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Constraint on Visual and Nonvisual Mammalian Opsins

Abstract: Animals have evolved light-sensitive G protein–coupled receptors, known as opsins, to detect coherent and ambient light for visual and nonvisual functions. These opsins have evolved to satisfy the particular lighting niches of the organisms that express them. While many unique patterns of evolution have been identified in mammals for rod and cone opsins, far less is known about the atypical mammalian opsins. Using genomic data from over 400 mammalian species from 22 orders, unique patterns of evolution for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 159 publications
(195 reference statements)
0
28
0
Order By: Relevance
“…Although the RGR is poorly conserved, it sustains the responsiveness of photoreceptor cells ( Upton et al, 2021 ). The mutant RGR causes many diseases, such as dominantly inherited peripapillary choroidal atrophy (c.824dupG, p. I276Nfs*77) ( Upton et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the RGR is poorly conserved, it sustains the responsiveness of photoreceptor cells ( Upton et al, 2021 ). The mutant RGR causes many diseases, such as dominantly inherited peripapillary choroidal atrophy (c.824dupG, p. I276Nfs*77) ( Upton et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the RGR is poorly conserved, it sustains the responsiveness of photoreceptor cells ( Upton et al, 2021 ). The mutant RGR causes many diseases, such as dominantly inherited peripapillary choroidal atrophy (c.824dupG, p. I276Nfs*77) ( Upton et al, 2021 ). Abnormal RGR proteins, including RGR-d (an exon-skipping splice variant), strongly inhibit cell growth in vitro ( Bao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…OPN5 is the most conserved non-visual opsin in mammals compared to OPN3 and OPN4, and is found in frogs, birds, and mammals 27,28 . Although Laurasiatheria, Afrotheria, Xenartheria, Euarchontoglire, and other mammals have different opsins related to visual information depending on their living environment, the fact that all these mammals have OPN4 and OPN5 suggests that OPN4 and OPN5 play a crucial role in controlling tissue functions in response to light environment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in the past two decades have strongly suggested that opsins in the retina play a special role in the photoentrainment of mammalian circadian rhythms [106,107,119]. In particular, the opsin family evolved prior to the evolution of image-forming visual systems, suggesting that the original role of opsins was nonvisual, including checking time-of-day information based on photoperiod, intensity, and wavelength of light [144].…”
Section: Circadian Photoentrainmentmentioning
confidence: 99%
“…As mentioned, reptiles utilize the parietal eye as a photoreceptor, which disappeared during evolution [128,141,150]. Consequently, it has been proposed that a photosensitive system may have evolved in mammal skin to compensate for parietal eye loss [127,144].…”
Section: Circadian Photoentrainmentmentioning
confidence: 99%